Impacts of climate change on bovine livestock production in Argentina - Rolla, Alfredo Luis (2019)
The study considers the most important livestock regions of Argentina and the correlation between livestock and climate units. The conceptual scheme designed to understand these effects of climate elements on cattle describes a basic direct action by the air temperature in the environment in which they develop, considering temperature as the limit for the distribution of breeds and other action through its effects on vegetation and forage resources that will be available. The work done here shows a shift of the livestock regions southward and eastward simultaneously in the region under consideration. This is a consequence of the displacement towards the south of the isotherm of 26 °C and towards the east of the humidity indices, co-incidentally with the displacement of the isohyets of 600 and 1200 mm. As a consequence of the climate change, according to the CCSM4 climate model, in the near and far future under two emission scenarios, the regions suitable for tropical livestock (breeds with high heat tolerance as the Bos indicus) will extend to the southeast, displacing and reducing the regions suitable for European breed cattle. The displacement of the higher rainfall area mainly to the east could benefit livestock production by increasing forage and reducing livestock feed requirements.